Covid-19 the pandemic that never should have happened and how to stop the next one - Mackenzie, Deborah (Hachette Books, 2020)
"Over the last 30 years of epidemics and pandemics, we learned every lesson needed to stop this coronavirus outbreak in its tracks. We heeded almost none of them. The result is a pandemic on a scale never before seen in our lifetimes. In this captivating, authoritative, and eye-opening book, science journalist Debora MacKenzie lays out the full story of how and why it happened: the previous viruses that should have prepared us, the shocking public health failures that paved the way, the failure to contain the outbreak, and most importantly, what we must do to prevent future pandemics. Debora MacKenzie has been reporting on emerging diseases for more than three decades, and she draws on that experience to explain how COVID-19 went from a potentially manageable outbreak to a global pandemic. Offering a compelling history of the most significant recent outbreaks, including SARS, MERS, H1N1, Zika, and Ebola, she gives a crash course in Epidemiology 101--how viruses spread and how pandemics end--and outlines the lessons we failed to learn from each past crisis. In vivid detail, she takes us through the arrival and spread of COVID-19, making clear the steps that governments knew they could have taken to prevent or at least prepare for this. Looking forward, MacKenzie makes a bold, optimistic argument: this pandemic might finally galvanize the world to take viruses seriously. Fighting this pandemic and preventing the next one will take political action of all kinds, globally, from governments, the scientific community, and individuals--but it is possible. No one has yet brought together our knowledge of COVID-19 in a comprehensive, informative, and accessible way. But that story can already be told, and Debora MacKenzie's urgent telling is required reading for these times and beyond. It is too early to say where the COVID-19 pandemic will go, but it is past time to talk about what went wrong and how we can do better"-- Provided by publisher.